MALADMINISTRASI DALAM PELAKSANAAN PUTUSAN PENGADILAN TATA USAHA NEGARA DALAM PERSPEKTIF UNDANG-UNDANG PELAYANAN PUBLIK - Riza, Dola (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
State administrative court decisions are carried out by revoking and/or issuing state administrative decisions. These activities in the Public Service Act are known as administrative services. Even so, there are still many maladministrations in implementing state administrative court decisions. in this study is how maladministration in the implementation of decisions of the State Administrative Court in the perspective of public service law. The type of research used is normative legal research. The legal data used are primary legal data, secondary legal data and tertiary legal data. The legal data collection technique used is document study. The legal data analysis technique used is a qualitative analysis technique. Based on the results of the study it can be concluded that 1) There is no synchronization and harmonization between Article 116 Paragraph (3), Paragraph (4) and Paragraph (6) of the State Administrative Court Act and Article 34 letter d of the Public Service Act.